Financial Reporting Timeliness, Information Quality, and Firm Performance: Examining the Mediating Role of Reporting Effectiveness - Rahel Junita (Manunggal Halim Jaya, 2026)
Timely and high-quality financial reporting has become increasingly important in improving organizational performance and supporting strategic decision-making. However, limited empirical evidence explains how reporting effectiveness mediates the relationship between financial reporting attributes and firm performance, particularly in emerging economies. This study aims to examine the effects of financial reporting timeliness and information quality on firm performance by investigating the mediating role of reporting effectiveness. A quantitative research design was employed using primary data collected from 100 financial statement users working in companies located in Medan, Indonesia. The census sampling technique was applied, and the data were analyzed using multiple linear regression with SPSS version 20. The results indicate that financial reporting timeliness, financial reporting quality, and reporting effectiveness each have positive and statistically significant effects on firm performance. Furthermore, reporting effectiveness significantly mediates the relationship between financial reporting quality and firm performance, indicating that high-quality financial information improves organizational outcomes when it is effectively communicated and utilized. These findings extend financial reporting literature by providing an integrated framework that links reporting quality, timeliness, and reporting effectiveness within a single analytical model. Practically, the study provides useful insights for managers, auditors, and policymakers in improving financial reporting systems to support sustainable organizational performance.